2015
DOI: 10.1089/neu.2014.3694
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy after Traumatic Brain Injury

Abstract: Chaperone-mediated autophagy (CMA) and the ubiquitin-proteasomal system (UPS) are two major protein degradation systems responsible for maintaining cellular homeostasis, but how these two systems are regulated after traumatic brain injury (TBI) remains unknown. TBI produces primary mechanical damage that must be repaired to maintain neuronal homeostasis. The level of lysosomal-associated membrane protein type 2A (LAMP2A) is the hallmark of CMA activity. The level of polyubiquitinated proteins (ubi-proteins) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…23,42,43 Among them, IL-10 is the most important because it exerts neuroprotective effects via suppressing the expression of various pro-inflammatory cytokines, such as IFN-γ, IL-1β, IL-2, IL-6 and TNF-α, as observed in stroke 23,44 and in TBI. 42,43,[45][46][47] MSCs may secrete IL-10 under specific conditions, such as inflammatory environments observed after brain injuries. 52 Also, they may stimulate the cells surrounding the injury and trigger the secretion of IL-10 and other neurotrophic factors.…”
Section: Discussionmentioning
confidence: 99%
“…23,42,43 Among them, IL-10 is the most important because it exerts neuroprotective effects via suppressing the expression of various pro-inflammatory cytokines, such as IFN-γ, IL-1β, IL-2, IL-6 and TNF-α, as observed in stroke 23,44 and in TBI. 42,43,[45][46][47] MSCs may secrete IL-10 under specific conditions, such as inflammatory environments observed after brain injuries. 52 Also, they may stimulate the cells surrounding the injury and trigger the secretion of IL-10 and other neurotrophic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that autophagy is activated in various animal models of the central nervous system, such as traumatic brain and spinal cord injury (Park et al, 2015;Li et al, 2015a), cerebral and spinal cord ischemia (Villamil-Ortiz and CardonaGomez, 2015;Li et al, 2015b), intracerebral hemorrhage (Yang et al, 2015), and neurodegeneration (Navone et al, 2015). In the model of cerebral ischemia, activated autophagy occured in different cell types such as neurons , astrocytes (Qin et al, 2010) and vascular endothelial cells (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an intracellular catabolic mechanism that maintains a balance between protein synthesis and degradation, which can both promote cell survival and induce cell death (autophagic cell death) depending on the specific pathological event. Accumulating evidence has demonstrated that autophagy activation is elevated in the central nervous system under stressed conditions (Park et al, 2015;Li et al, 2015a;Villamil-Ortiz and Cardona-Gomez, 2015;Yang et al, 2015). As shown in the previous studies, autophagy plays an important role in spinal cord injury (Baba et al, 2009;Seo et al, 2015;Fujita et al, 2015); however, its expression change and mechanism after spinal cord I/R injury are largely unknown.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, autophagy has been demonstrated to be an important therapeutic mechanism for injuries of CNS such as SCI and several CNS degeneration diseases such as Alzheimer's disease. Accumulating evidence has shown that autophagy is induced after SCI, and the impairment of autophagy has been addressed to aggravate the secondary injury. The AMP‐activated protein kinase (AMPK) acts as an energy sensor responding to stress conditions such as oxidative stress and deprivation of nutrition, which also acts as a key player in autophagy.…”
Section: Introductionmentioning
confidence: 99%